Distance education for Caribbean social studies teachers - Morris, Pam
This article outlines a distance education Certificate in Education programme for teachers in the Caribbean, administered by The University of the West Indies (UWI) in association with the University of London. It highlights the learning modules of the Teaching of Social Studies option. The article also examines student evaluation and explores problems that arise in teleconferencing teaching
Keywords: Social studies teachers